2015
DOI: 10.1089/apc.2015.0133
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure and Self-Efficacy Among HIV-Positive Men Who Have Sex with Men: A Comparison Between Older and Younger Adults

Abstract: Men who have sex with men (MSM) continue to be disproportionately affected by HIV in the US. HIV among older adults also continues to be an important public health problem. Age is associated with disclosure of HIV serostatus and self-efficacy for condom use. However, studies examining self-efficacy and disclosure among older MSM (age 50 and older) living with HIV are lacking. The aim of this study was to assess the associations between being 50 and older, and disclosure behaviors, intentions and attitudes, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…10 In addition, beliefs that sex is safer as a result of ART and HIV suppression were also associated with nondisclosure. Results from the multivariable model showed that these three factors, disclosure self-efficacy, risk reduction communication skills, and infectiousness beliefs, independently contribute to condomless sex in the context of nondisclosure to nonconcordant sex partners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In addition, beliefs that sex is safer as a result of ART and HIV suppression were also associated with nondisclosure. Results from the multivariable model showed that these three factors, disclosure self-efficacy, risk reduction communication skills, and infectiousness beliefs, independently contribute to condomless sex in the context of nondisclosure to nonconcordant sex partners.…”
Section: Discussionmentioning
confidence: 99%
“…That is, greater disclosure of HIV status was associated with practicing safer sexual behaviors and this was true across subgroups of men who have sex with men, men who have sex with women, and women who have sex with men. In another recent study, Brown et al 10 reported that among men who have sex with men, older men (age 50 and older) were less likely to disclose their HIV status than younger men and older men were less self-efficacious in their perceived ability to disclose.…”
Section: Introductionmentioning
confidence: 99%
“…Since the introduction of widespread antiretroviral therapy (ART), evidence on the association between non-disclosure and condom use among HIV-diagnosed MSM has been mixed; certain studies found that nondisclosure was associated with higher prevalence of condomless sex or condomless sex with HIV-serodifferent partners (CLS-D) (Cook, Valera, & Wilson, 2015;Hirsch Allen et al, 2014;Klitzman et al, 2007;Morin et al, 2005;Parsons et al, 2005;Simon Rosser et al, 2008;Wilson et al, 2016), others found no evidence of an association (Kalichman, DiMarco, Austin, Luke, & DiFonzo, 2003;Marks & Crepaz, 2001;Poppen, Reisen, Zea, Bianchi, & Echeverry, 2005;Przybyla et al, 2014;Simoni & Pantalone, 2004;van Kesteren, Hospers, van Empelen, van Breukelen, & Kok, 2007), while some reported that non-disclosure was linked to condom-protected sex (Abler et al, 2015;Klitzman et al, 2007;Serovich et al, 2018;Simon Rosser et al, 2008). Studies that examined levels of disclosure to sexual partners showed that those who disclose to some partners tend to report higher levels of condomless sex compared to those who disclose to none or most/all partners (Abler et al, 2015;Brown, Serovich, Kimberly, & Umasabor-Bubu, 2015;Durham et al, 2013;Parsons et al, 2005;Simon Rosser et al, 2008). Only two studies from the UK (2008-09) (Elford, Ibrahim, Bukutu, & Anderson, 2008;Fox et al, 2009) showed prevalence estimates of disclosure to sexual partners, but none examined associations between disclosure and condomless sex.…”
Section: Introductionmentioning
confidence: 99%
“…Simple and multiple linear regression models were used to determine the association between vengeance and disclosure behavior, attitudes and intention scores. Prior research has shown that age tends to have positive [15] and negative [16, 17] associations with HIV disclosure depending on how age is operationalized [16]. Age [4, 7] and knowing source of infection [7] have been shown to be associated with vengeance.…”
Section: Methodsmentioning
confidence: 99%